Alternate arm converter energy balancing under parameter variation - Wickramasinghe, Harith R. (2020)
Energy balancing of the alternate arm converter (AAC) is a major challenge and overlap period-based circulating current control methods are commonly used. Component parameter variation occurs due to tolerances, component aging, and internal faults leading to stored energy imbalances of modular voltage source converter (VSC) topologies. If not controlled, such variations can severely impact the operation of the AAC. Hence, component parameter variation is a key consideration for energy balancing of all sorts of modular VSC topologies, but has not been addressed in the existing literature for the AAC. This paper investigates the energy balancing capability of the AAC in high-voltage direct current (HVDC) applications under component parameter variations and proposes a compensation method to further improve its energy balancing performance. The effectiveness of the proposed method is verified in a real-Time model of an AAC-HVDC transmission system from widely accepted existing CIGRE benchmark models.